2004
DOI: 10.1088/0953-8984/16/21/008
|View full text |Cite
|
Sign up to set email alerts
|

Strain-accelerated HF etching of AlAs for epitaxial lift-off

Abstract: Epitaxial lift-off (ELO) is a process which allows for the separation of a single crystalline III/V thin film or device from the substrate it was deposited on. This process is based on the selective etching of an intermediate AlAs release layer in an aqueous HF solution. The lateral etch rate of the AlAs release layer through a narrow crevice in the weight-induced epitaxial lift-off (WI-ELO) process is much larger than observed for unobstructed planar AlAs layers. It is possible that this increase in etch rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Therefore, during the last few years, the lateral etch rate and the release layer have been under serious investigation as a function of the process parameters. [7][8][9][10][11][12] The etch rate might be limited either by the reaction kinetics at the etch front or by the diffusion of the etchant (HF) and reaction products toward and from this front. For both situations, it is essential to know the reaction formula of AlAs with an aqueous HF solution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, during the last few years, the lateral etch rate and the release layer have been under serious investigation as a function of the process parameters. [7][8][9][10][11][12] The etch rate might be limited either by the reaction kinetics at the etch front or by the diffusion of the etchant (HF) and reaction products toward and from this front. For both situations, it is essential to know the reaction formula of AlAs with an aqueous HF solution.…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters that have been investigated as strain applied to the wafer during the lift-off process [17], n-or p-type doping levels in the release layer [3], aluminium fraction x (must be >0.6) in the Al x GaAs release layer [3], the addition of a surfactant or anti-foaming agent [22] do not influence the etch rate to the same extent. In summary, it can be concluded that for optimized practically applicable settings an etch rate exceeding 30 mm/hr is feasible, resulting in a lift-off time of around 3 hours for a 4 inch wafer.…”
Section: Key Process Parametersmentioning
confidence: 99%
“…With this goal in mind the work on ELO at the Radboud University Nijmegen was started in the mid 1990s. An ELO setup was developed to allow for a systematic investigation on the basic parameters that determine the etch rate [3,15,16,17,18,19] and a model to describe the process was developed [20,21]. By making some essential modifications to the original ELO method, like the use of a temporary flexible carrier and applying a controlled force to allow the etchant to reach the etch front, the etch rate increased by more than a factor of 100 to rates well above 30 mm/h [16,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…6 Etching of the sample was undertaken using a mixture of NH 4 OH:H 2 O 2 :H 2 O (2:1:10), reported to selectively etch GaAs over AlAs, and a 10% mixture of HF, reported to selectively etch AlAs over GaAs. 7 The procedure followed was to place the sample in the NH 4 OH:H 2 O 2 :H 2 O solution for 5s followed by 10s in the 10% HF solution. After rinsing and drying the sample was immediately measured in the FTIR.…”
mentioning
confidence: 99%